Amply Cofinitely Essential Supplemented Modules - , Berna Koşar; , Celil Nebiyev (Archives of Current Research International, 2019)
Let M be an R−module. If every cofinite essential submodule of M has ample supplements in M then M is called an amply cofinitely essential supplemented module. In this work some properties of these modules are investigated. Let M be a projective and cofinitely essential supplemented R−module. Then every M−generated R−module is amply cofinitely essential supplemented.